Mālama nā makua i nā keiki me ka hānō: Native Hawaiian parents caring for their children with asthma - May K. Kealoha; Merle Kataoka-Yahiro (JMIR Publications, 2017)
Native Hawaiian children have the highest prevalence rate of asthma among all ethnicities in the State of Hawai'i. Literature is limited regarding native Hawaiian parents' perception and experience caring for their children with asthma. The purpose of this study is to explore contemporary native Hawaiian parents' perspective and experience of caring for their children with asthma in the context of uncertainty. We applied a descriptive qualitative approach by means of directed content analysis using focus groups. Directed content analysis applied Mishel's Uncertainty in Illness Theory to guide data collection, organization, and analysis. We found that parents' personal stories about their children to be rich and enlightening. Findings verified that native Hawaiian parents experience uncertainty regarding asthma care as commonly described in the literature. Contextual influences including indigenous worldview and cultural values affected native Hawaiian parents' perceptions and experiences with conventional asthma care. Unique findings involved the etiology of asthma, features of social support ('ohana), and differentiation between Western medicine and traditional healing practices. As nurses focus on supporting the family's cultural values and preferences related to asthma care and alternative remedies, native Hawaiian parents' care of their children with asthma will be strengthened.